Enzymatic-Assisted Extraction, Physicochemical Characteristics Evaluation and Structural Elucidation of Antioxidative Protein-Polysaccharides Gum from Durio zibethinus Murray Seeds - Mohd Yusof, Hasif Ilyasa; Azmi, Saiful Mohammad Nizam; Mapik, Samsiah; Mohd Yunos, Nuraina Sofea; Ong Gim Ming, Sandy; Yap Ying Hui, Ray; Tan, Huay Ying (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Durio zibethinus Murray or durian is an exotic tropical fruit native to Southeast Asia. Durian seeds (DS) which mainly composed of mucilage and fibers are generally discarded as agricultural waste post-consumption, yet have promising characteristics as innovative food ingredients with high economic value. Enzymatic-assisted extraction of protein-polysaccharide gum (E-PG) from DS improved the yield efficiency by 4.36-fold with 3.0% celullase, and moisture content in the range of 4-6% (dry weight). Proximate composition for the total carbohydrate, dietary fiber, sugar and crude protein were found at 74.4, 24.0, 4.0 and 10.1 g/100 g of sample. E-PG recorded higher water-holding and oil-holding capacities, and solubility percentage as compared with non-enzymatically extract of protein-polysaccharide gum (N-PG) and DS flour. Physicochemical characteristics revealed E-PG was 2.52-fold lower than xanthan gum (XG AD). Validation on E-PG2.52-fold revealed that the viscosity matched the quality of XG AD. Characterization with HPLC-RID, FT-IR and 1N-NMR highlighted typical distribution of polysaccharides and protein, thus confirming the presence of protein/polysaccharides-based components in E-PG and N-PG. Antioxidant evaluation revealed that E-PG and E-PGslurry scavenged ABTS•+-radicals at an IC50 of 5.759±0.719 and 6.083±0.131 mg/mL, and ORAC values of 57867±2873 and 70191±6291 µM TE/g, respectively, whereas ORAC activity for XG AD was not detected. The recovery of water-soluble protein-polysaccharides gum from non-traditional source like DS via deployment of enzymatic-assisted extraction protocol has improved the extraction yield and enhanced antioxidative capacity of the gum, greater than commercial gums. Findings may significantly influence the food and/or nutraceutical industries on the utilization of value-added and innovative food ingredients in their product formulation.